“Falling at the First Hurdle” : Phenomenological Analysis of Students Suicide in Indonesia from the Perspective of Developmental Psychopathology and Its Implications for School Counseling - Afina Mutmainnah; Donny Hendrawan (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to analyze the phenomenon of student suicide in Indonesia in 2023 from the perspective of developmental psychopathology and suggest its implications for school counseling. This qualitative research employed a phenomenology approach. The data sources were secondary, obtained from suicide news articles on national and regional online news sites, and analyzed using reflexive thematic technique. The research results indicated 15 cases with 5 themes depicting the phenomenon of student suicide, including 1) accessible places and methods, 2) leaving messages or signs, 3) the severity of family conditions, 4) internalizing many things, and 5) dangerous peer influences. The concept of equifinality could be illustrated from the analyzed phenomena. The internalizing problems experienced by the victims may stem from the relationship patterns between parents and students and/or students and peers, which appear to dominantly underlie these cases. The research findings recommend implications for strengthening holistic counseling programs involving various members in the school environment.